Activation of 5-HT and NR2B contributes to visceral hypersensitivity in irritable bowel syndrome in rats - Chen, Ming-Xian (Am J Transl Res, 2016)
The roles of 5-hydroxytryptamine (5-HT) and spinal N-methyl-D-aspartic acid receptor 2B (NR2B) in visceral hypersensitivity were investigated. A rat model with irritable bowel syndrome (IBS) was established by intracolonic injections of acetic acid onpost-natal days 8-21. Rats were randomly divided into five groups: normal intact (control) group, IBS model group, Ro25-6981-treated IBS rats (Ro25-6981, a NR2B antagonist) group, amitriptyline-treated IBS rats (amitriptyline, a 5-HT antagonist) and Ro25-6981 plus amitriptyline-treated IBS rats (Ro25-6981+amitriptyline) group. The expressions of 5-HT, NR2B, 5-HT2AR, 5-HT7R, SERT, TNF-α and IL-1β in colon, dorsal root ganglion (DRG) and hypothalamus, respectively, were measured by Immunohistochemical staining, Real-Time Reverse Transcription-PCR and Western blotting. Our results showed increased DRG and hypothalamus expression of 5-HT, NR2B, 5-HT2AR, 5-HT7R in IBS model group and decreased expression of those in Ro25-6981 and amitriptyline alone or both treatment groups. Moreover, SERT expression was decreased in colorectal, DRG and hypothalamus of ISB model rats, but increased by Ro25-6981 and amitriptyline alone or both treatments. Ro25-6981 and amitriptyline treatment also decreased colorectal expression of TNF-α and IL-1β induced by IBS model. In conclusion, activation of 5-HT and NR2B may play a crucial role in visceral hypersensitivity in irritable bowel syndrome in rats.